Oral delivery of the intracellular domain of the insulinoma-associated protein 2 (IA-2ic) by bacterium-like particles (BLPs) prevents type 1 diabetes mellitus in NOD mice - Mao, Ruifeng; Yang, Menglan; Yang, Rui; Chen, Yingying; Diao, Enjie; Zhang, Tong; Li, Dengchao; Chang, Xin; Chi, Zhenjing; Wang, Yefu (Drug delivery, 2022)
Antigen-specific immune tolerance, which possesses great potential in preventing or curing type 1 diabetes mellitus (T1DM), can be induced by oral vaccination with T1DM-related autoantigens. However, direct administration of autoantigens via oral route exhibits a low tolerance-inducing effect as a result of the digestion of protein antigens in the gastrointestinal tract (GIT) and therefore, a large dosage of autoantigens may be needed. In this study, bacterium-like particles (BLPs) made from food-grade lactic acid bacteria were used to deliver the intracellular domain of the insulinoma-associated protein 2 (IA-2ic). For this purpose, BLPs-IA-2ic vaccine in which IA-2ic bound to the surface of BLPs was constructed. BLPs enhanced the stability of the delivered IA-2ic based on the stability analysis in vitro. Oral administration of BLPs-IA-2ic significantly reduced T1DM incidence in NOD mice. The mice fed BLPs-IA-2ic exhibited a significant reduction in insulitis and preserved the ability to secrete insulin. Immunologic analysis showed that oral vaccination with BLPs-IA-2ic induced antigen-specific T cell tolerance. The results revealed that the successful induction of immune tolerance was dependent on the immune deviation (in favor of T helper 2 responses) and CD4 + CD25 + FoxP3 + regulatory T cells. Hence, oral vaccination with BLPs-IA-2ic shows potential for application in preventing T1DM.